Harold M. Hyman, William M. Wiecek, Equal Justice wader Law — Constitutional Development 1835-1875, Harper Row Publishers, New York 1982, ss. XVIII+572 - Bryk, Andrzej (Czasopismo Prawno-Historyczne, 1984)
Recenzja: Harold M. Hyman, William M. Wiecek, Equal Justice wader Law — Constitutional Development 1835-1875, Harper Row Publishers, New York 1982, ss. XVIII+572.